Comparison of processed results of GPS and GLONASS data - Hải, Vy Quốc (Vietnam Journal of Earth Sciences, 2013)
The GLONASS system that has grown over time, has met the geodetic and navigation applications. The signal of both GLONASS and GPS system has been collected by a new type of receiver at the same time. This has opened the ability to compare and analyze results of GLONASS and GPS data processing.On this occasion, the GPS data of seven daily sessions (in large spatial scales - the distance about 4500km) was processed separately GLONASS and GPS data with Bernese advanced software. Basing on comparison and analysis results, some conclusions can make:-Baseline computed from the GPS data is more accurate and reliable than the one from GLONASS data.-However, the coordinates adjusted from the two above types of data can be considered as homogeneous with relative difference better 1/60 000 000.